PENGEMBANGAN BUKU MEDIA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Elvi mailani (Universitas Negeri Medan, 2018)
Abstract: Development of Elementary Mathematics Learning Media Books.This study aims to compile a textbook for elementary mathematics learning forstudents of the faculty of education in Medan State University. The elementaryschool mathematics learning media book was compiled based on the results ofobservations at the time of the lecture. It was seen that the learning resources usedby lecturers were dictates that had been compiled for a long time without upgradingthe material contained in the dictate so that it was in accordance with the curriculumcurrently in use. The specific purpose of this study is: to develop elementarymathematics learning media books that will be used by faculty of education sciencestudents in the lecture process to replace the dictates they have been using. Thisresearch uses Developmental Research. The subjects of this study were studentsfrom the Medan State University education science faculty. The results targeted inthis study are effective elementary school mathematics learning media books whichwill later be used by students of the education faculty of Medan State University,replacing the long-used dictate.Keywords: Books, Mathematics, Learning Media, Elementary SchoolsAbstrak: Pengembangan Buku Media Pembelajaran Matematika SekolahDasar. Penelitian ini bertujuan menyusun buku media pembelajaran matematika SDbagi mahasiswa fakultas ilmu pendidikan Universitas Negeri Medan. Buku mediapembelajaran matematika SD ini disusun berdasarkan hasil observasi pada saatperkuliahan dilihat bahwa sumber belajar yang dipakai dosen adalah diktat yangsudah sangat lama disusun tanpa pernah ada direvisi untuk menupgrade materi yangterdapat dalam diktat tersebut sehingga sesuai dengan kurikulum yang sedangdipakai pada saat ini. Tujuan khusus penelitian ini adalah: mengembangkan bukumedia pembelajaran matematika SD yang nantinya akan dipakai oleh mahasiswafakultas ilmu pendidikan dalam proses perkuliahan menggantikan diktat yangselama ini mereka pakai. Penelitian ini menggunakan penelitian pengembangan(Developmental Research). Subyek penelitian ini adalah mahasiswa fakultas ilmupendidikan universitas Negeri Medan. Hasil yang ditargetkan pada penelitian iniadalah buku media pembelajaran matematika SD yang efektif yang nantinya akandipakai oleh mahasiswa fakultas ilmu pendidikan Universitas Negeri Medan,menggantikan diktat yang sudah lama dipakai.Kata Kunci : Buku, Matematika, Media Pembelajaran, Sekolah Dasar